Methodological Challenges by (New) Media Journal for Religion, Film and Media - Christian Wessely (Journal for Religion, Film and Media, 2015)
The classical concept of media analysis depends to a large extent on linearity, but modern interactive media are mostly non-linear. Roger Odin has suggested a method for working with such interactive media; however, the approach he suggests creates a new problem. What would be an appropriate way to deal with the dilemma of balancing sufficient intersubjectivity and concessions to non-linearity?